Effective Gradle implementation - Vanderwerf, Ryan.; Fox, Lee.; Safari eBooks ([S.l.] : Packt Pub., 2014)
"Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. If you are a developer, devops engineer, build engineer, or IT administrator and wish to effectively implement Gradle in your projects, this course is for you. The course takes you through the installation process and how to set up your projects followed by dependency management, IDE integration, and plugin implementations. You also learn to deploy and publish your application. Basic Java development knowledge is a prerequisite. This example-driven video tutorial shows you how to effectively implement Gradle in your projects through a variety of plugins and integration techniques."--Resource description page.
Title from title screen (viewed Oct. 1, 2014).
Presenter, Ryan Vanderwerf and Lee Fox.
Keywords: Computer software -- Development -- Management; Computer programming -- Management; Open source software; Computer software -- Validation; Computer software -- Verification; Electronic books